Central growth hormone action regulates neuroglial and proinflammatory markers in the hypothalamus of male mice. (29th May 2023) - Wasinski, Frederick; Tavares, Mariana R.; Gusmao, Daniela O.; List, Edward O.; Kopchick, John J.; Alves, Guilherme A.; Frazao, Renata; Donato, Jose
Highlights: GH-deficient mice show decreased brain expression of Nes, Gfap, Iba1, Adgre1, and Tnf. GH overexpression increases brain expression of Nes, Gfap, Iba1, Adgre1, and Rax. Liver-specific GHR ablation increases the mRNA levels of Gfap, Iba1, and Tnf. Increased GH secretion causes hypothalamic inflammation, independent of IGF-1 levels. Brain GHR signaling is necessary to modify the expression of several glial markers. Abstract: Growth hormone (GH) action in specific neuronal populations regulates neuroendocrine responses, metabolism, and behavior. However, the potential role of central GH action on glial function is less understood. The present study aims to determine how the hypothalamic expression of several neuroglial markers is affected by central GH action in male mice. The dwarf GH- and insulin-like growth factor-1 (IGF-1)-deficient Ghrhr lit/lit mice showed decreased mRNA expression of Nes (Nestin), Gfap, Iba1, Adgre1 (F4/80), and Tnf (TNFα) in the hypothalamus, compared to wild-type animals. In contrast, transgenic overexpression of GH led to high serum GH and IGF-1 levels, and increased hypothalamic expression of Nes, Gfap, Adgre1, Iba1, and Rax . Hepatocyte-specific GH receptor (GHR) knockout mice, which are characterized by high serum GH levels, but reduced IGF-1 secretion, showed increased mRNA expression of Gfap, Iba1, Tnf, and Sox10, demonstrating that the increase in GH levels alters the hypothalamic expression of glial markers associated with neuroinflammation, independently of IGF-1. Conversely, brain-specific GHR knockout mice showed reduced expression of Gfap, Adgre1, and Vim (vimentin), indicating that brain GHR signaling is necessary to mediate GH-induced changes in the expression of several neuroglial markers. In conclusion, the hypothalamic mRNA levels of several neuroglial markers associated with inflammation are directly modulated by GHR signaling in male mice.